PENGARUH ETHICAL LEADERSHIP TERHADAP INNOVATION WORK BEHAVIOR DENGAN LMX DAN SELF EFFICACY SEBAGAI VARIABEL MEDIASI - Febriyanti, Mellyna Dwi; Nugroho, Sidiq Permono (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
The purpose of this study is to analyse the effect of Ethical Leadership on Innovation Work Behavior with Lmx and Self Efficacy as mediating variables. This research uses quantitative methods. The data used in this research is primary data. The population in this study were employees of the Surakarta City Population and Civil Registration Office and the Surakarta City Regional Planning, Research and Development Agency (BAPPELBANGDA) Office. The sample technique used in this research is purposive sampling. In this study, the minimum sample taken was 140 respondents based on malhorta calculation. Questionnaire distribution is the data collection method in this study. The survey was made using a frequency scale and Likert scale format. Partial Least Square (PLS) data analysis using SMARTPLS software is the method used in this study. The results of this study are Ethical Leadership has a significant positive effect on Innovation Work Behaviour. Ethical Leadership has a significant positive effect on Leader Member Exchange. Ethical Leadership has a significant positive effect on Self Efficacy. Leader Member Exchange has a significant positive effect on Innovation Work Behaviour. Self Efficacy has a significant positive effect on Innovation Work Behaviour. Ethical Leadership has a significant positive effect on Innovation Work Behaviour mediated by Leader Member Exchange. Ethical Leadership has a significant positive effect on Innovation Work Behaviour mediated by Self Efficacy.